Energy Sector Transformation Issues and Options for the UNFCCC Negotiations - Hood, Christina (OECD/IEA Climate Change Expert Group Papers, 2014)
A key element in the success of limiting mean global surface temperature rise to below 2°C will be transformation of the energy sector globally. In addition to implementing already-available options for more efficient use of energy and low-emissions energy supply, action is needed now to put in place the conditions for longer-term structural change to low-emissions energy systems. This transformational change will involve linkages between actions, institutions, and processes, both inside and outside the UNFCCC framework. This paper explores how the 2015 climate agreement, along with the nationally-determined contributions that Parties make under it, could drive energy sector transformation in addition to tracking greenhouse gas outcomes